Thành phần loài vi khuẩn Lam (Cyanobacteria) trong đất trồng lúa ở một số xã thuộc huyện Nghĩa Đàn, tỉnh Nghệ An - Ha, Le Thi Thuy (VNU Journal of Science: Natural Sciences and Technology; Vol 33 No 2DO - 10.25073/2588-1140/vnunst.4499, 2017)
THE SPECIES COMPOSITION OF CYANOBACTERIA IN RICE FIELDS OF NGHIA DAN DISTRICT, NGHE AN PROVINCE Nguyen Canh Hieu et al. Nghia Dan is a mountainous district of Nghe An province, stretching from 19 0 13’ to 19 0 33’ north latidute and between 105 0 18’ to 105 0 35’ east longitude. In August and December 2014 and in May 2015 we have investigated the species composition of Cyanobacteria distributing in rice fields of Nghia Dan district. We have found 40 species and subspecies in soil samples collected in 4 communes: Nghia Hung, Nghia My, Nghia Lam and Nghia Thuan. The most diverse genera were Oscillatoria (14 species and subspecies), Anabaena (6), Phormidium (5). There are 10 species and subspecies cyanobacteria contain heterocyst cells. Sorenxen coefficients between the sampling phases were from 0.82 to 0.88. Our study also showed that the numbers of species distributing at sampling sites were from 19 to 29 species .